Technical and tactical skills building in modern Greco-Roman wrestling supported by motivation-and-compulsion system - Boltikov, Yu. V.; Solomakhin, O. B.; Konovalov, I. E. (Theory and Practice of Physical Culture, 2018)
The study considers the high priority problem of the technical and tactical skills building in modern Greco-Roman wrestling. The study was performed at `Vityaz` Children and Youth Sport School (CYSS) in Naberezhnye Chelny. Subject to the study were junior Greco-Roman wrestlers split up into two Experimental and two Reference Groups (EG1, EG2, RG1 and RG2) of 26 people each. The Reference Groups were trained as required by the standard CYSS program; and the Experimental Groups were trained as required by the A.S. Kuznetsov`s frame technical skills building program supported by a motivation-and-compulsion system. The technical progress facilitating motivation-and-compulsion system of the authors` design implies a harmonious combination of competitive and technical standards for excellence in the training process with due sport qualification and technical categorizing process. Benefits of the motivation-and-compulsion system have been tested for 4 years by the following test criteria: technical skills versatility; activity rate; action success (quantitative) rate; action efficiency (qualitative) rate; and scoring rate. It should be noted that the Experimental and Reference Groups were virtually the same in the physical fitness rates prior to the experiment. After the first, second and third years of the model piloting experiment, the groups showed progress in every test rate, with the statistically significant intergroup differences. In the fourth year of the experiment, the groups still showed progress in every test rate, with the Experimental Group demonstrating significant advantages in the tests. Therefore, the motivation-and-compulsion system was found beneficial for the Greco-Roman wrestlers` educational and training process as verified by the EG progress in the competitive technical skills versatility, technical and tactical skills rates and competitive success rates.